Toward tunable advantages of quantum-like teams: the physics of interdependent teams to “squeeze” uncertainty - Lawless, William (Frontiers in Physics, 2026)
PurposeThe aim of this study is to provide a mathematical physics of entropy to organize and operate teams, whether teams are composed of humans, human–machine–AI, or any combination thereof.MethodWe review three (3) case studies and two (2) field studies of interdependence. The first case study concerns 7-year-long oscillations between the U.S. Department of Energy (DOE) and the Nuclear Regulatory Commission (NRC), which ended when South Carolina’s Department of Health and Environmental Control (DHEC) requested the public’s help. The second case study addresses randomness in business merger decisions. The third case study examines the validation crisis in social psychology, illustrated by the contrast between self-reports of suicidal ideation and suicide. The first field study explores the advantages under freedom versus command decision making (CDM), and the final field study addresses the physics of time-energy uncertainty.DataGuided by theory, the data provide information from the three case studies to test interdependence theory. For the two field studies, data are drawn from international data bases (e.g., the UN and the World Bank).ResultsLimited support is provided for classical coupled harmonic oscillators; in comparison, significant support is found for interdependent (quantum-like) teamwork.SignificanceThis study reviews and replicates earlier studies and generalizes findings to energy–time uncertainty relationships.